Modal analysis of motorized spindle using finite element method - Knežev, Miloš; Živkovic , Aleksadar; Marinković, Dejan; Mladjenović, Cvijetin; Andrei , Calin; Ilić, Vojin (Journal of Production Engineering, 2023)
Dynamic market conditions shows contant need to significantly shorten the time cycle of the product design phase, with demands for the lowest possible price and highest possible quality. Motorized spindle is already widely used as the main spindle of modern machine tools. Predict dynamic characteristic through numerical simulations is trend among machine tool manufacturers, especially when high accuracy is involved. Finite element method (FEM) is the most commonly used method for analyzing the dynamic behavior of the main spindle. In this work, a model was developed based on the finite element method. The obtained results are compared with experimental test.